Sodium electric hard carbon negative electrode material taking coconut shell as raw material
By using coconut shells as raw material to prepare sodium electrohard carbon negative electrode materials, combined with specific preparation steps and raw material ratios, the problems of low efficiency and poor circulation stability of existing sodium ion battery are solved, and efficient and stable electrochemical performance is achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411961939.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sodium ion batteries have low efficiency and poor cycle stability, which is difficult to apply in practice. The hard carbon materials on the market are costly and complex in preparation, which is not conducive to industrial production.
The sodium electrohard carbon negative electrode material with coconut shell as raw material is used, and the biomass hard carbon micropowder is prepared through specific preparation methods, including the preparation and activation, modification and carbonization steps of coconut shell carbonization material, and combined with the reasonable ratio of conductive agents, binders and tackifiers to form excellent electrochemical properties.
It achieves the effects of large reversible specific capacity, high Coulomb efficiency and excellent circulation performance in sodium batteries. It has simple process and convenient operation and control, and is suitable for large-scale production, reducing equipment dependence and energy consumption.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a sodium-ion battery hard carbon negative electrode material using coconut shell as a raw material. Background Art
[0002] Sodium-ion batteries are considered to be a promising alternative to lithium-ion batteries due to their abundant sodium content in the earth's crust, their high energy density and environmental friendliness. They are expected to be used in large-scale energy storage and smart grids. However, current sodium-ion batteries face technical defects such as low coulombic efficiency and poor cycle stability, making them difficult to use in practice. Developing improved negative electrode materials is the key to improving the performance of sodium-ion batteries and extending battery life.
[0003] Hard carbon materials are considered to be the best choice for negative electrode materials for sodium ion batteries. At present, hard carbon materials are mainly made of biomass charcoal such as coconut shells, starch, straw, bamboo, etc. This type of biomass charcoal usually has well-developed pores, a wide range of sources, and low cost, but its structure is not easy to control, and the surface defects of biomass charcoal are large. Its structure is mainly composed of mesopores and macropores, and its adsorption capacity for sodium ions is weak, resulting in low reversible capacity and poor conductivity. In addition, the preparation cost of hard carbon materials on the market is high, the operation is complicated, and it is not conducive to industrial production. The capacity of the hard carbon materials obtained is also low, and the coulombic efficiency and cycle performance are not ideal.
[0004] In order to solve the above problems, a Chinese invention patent with authorization announcement number CN116344803B discloses a hard carbon negative electrode material for sodium ion batteries and a preparation method thereof. The negative electrode material comprises, by weight, 100 parts of hard carbon micropowder, 6-8 parts of conductive additive and 10-12 parts of binder; the hard carbon micropowder is carbonized with polyvinyl alcohol and a self-made intercalation support matrix as carbon sources, the intercalation support matrix introduces silicon oxygen rings through tetramethyltetravinylcyclotetrasiloxane, and structural defects are formed after carbonization, which is conducive to the embedding of sodium ions with larger radius, thereby increasing the sodium storage capacity of the hard carbon material, and the sulfur-containing structure is introduced through mercaptoethanol modification, and the antimony element is fixed by its chelation effect, and antimony doping is introduced to the periphery of the molecule, which is combined with carbon to form an intercalation layer, thereby increasing the carbon layer spacing, and the antimony-carbon composite formed by carbonization has excellent conductivity, which is conducive to the migration of sodium ions between layers; the hard carbon micropowder is applied to the negative electrode of the sodium ion battery, and has good comprehensive performance of specific capacity, first effect and stability. However, its reversible specific capacity, coulombic efficiency and cycle performance in sodium batteries still need to be further improved.
[0005] It can be seen that the development of a sodium battery hard carbon negative electrode material made of coconut shell as raw material, which has excellent electrochemical properties, good process controllability, large reversible specific capacity, high coulombic efficiency and excellent cycle performance for use in sodium batteries, meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the sodium battery field. Summary of the invention
[0006] The main purpose of the present invention is to provide a sodium battery hard carbon negative electrode material using coconut shell as raw material, which has excellent electrochemical performance, good process controllability, large reversible specific capacity, high coulombic efficiency and excellent cycle performance when used in sodium batteries.
[0007] To achieve the above purpose, the present invention provides a sodium battery hard carbon negative electrode material using coconut shell as raw material, which comprises the following raw materials in parts by weight: 100 parts of biomass hard carbon powder, 2-4 parts of conductive agent, 3-5 parts of binder, and 0.8-1.2 parts of viscosity enhancer.
[0008] Preferably, the method for preparing the biomass hard carbon powder comprises the following steps: Step S1, preparation and activation of coconut shell carbonized material: using coconut shell as biomass raw material and subjecting it to high temperature pyrolysis to prepare coconut shell carbonized material; then heating the coconut shell carbonized material to 550-700°C at a heating rate of 6-8°C / min, keeping the temperature for 1-3h under a nitrogen atmosphere, cooling to room temperature, then alkali washing, water washing, drying, and crushing to obtain activated coconut shell carbonized material; Step S2, modification: the activated coconut shell carbonized material prepared in step S1 is dispersed in a high boiling point solvent, and then methacryloxypropyl triethoxysilane, bis(1-vinyl imidazole-2-) ketone, 2,4,6-trivinyl cycloboroxane, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, and initiator are added thereto, and the mixture is stirred and reacted at 60-70° C. for 3-6 hours in an inert gas atmosphere. After the reaction is completed, the solvent is removed by rotary evaporation; the crude product is then immersed in a sodium telluride aqueous solution at 50-60° C. for 10-20 hours, and water is removed by rotary evaporation again to obtain the modified coconut shell carbonized material; Step S3, carbonization: the modified coconut shell carbonized material is placed in a muffle furnace, roasted at 200-220°C for 1-3h, and then kept at 300-330°C for 2.5-4h, then transferred to a tubular furnace, heated to 800-860°C under argon atmosphere, kept warm for 1-2h, and then continued to heat to 1210-1330°C for 1-2h, cooled and dry ground to obtain biomass hard carbon powder.
[0009] Preferably, the high temperature pyrolysis in step S1 is specifically: heating to 1000-1300° C. at a heating rate of 3-6° C. / min, and keeping the temperature for 1-2 hours.
[0010] Preferably, the average particle size of the activated coconut shell carbonized material in step S1 is 5-10 μm.
[0011] Preferably, the mass ratio of the activated coconut shell carbonized material, high boiling point solvent, methacryloxypropyl triethoxysilane, bis(1-vinyl imidazole-2-) ketone, 2,4,6-trivinyl cycloboroxine, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, and initiator in step S2 is (3-5):(10-20):(0.1-0.3):0.1:0.2:0.1:0.1:(0.04-0.06).
[0012] Preferably, the high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone.
[0013] Preferably, the initiator is azobisisobutyronitrile.
[0014] Preferably, the inert gas is any one of nitrogen, helium, neon and argon.
[0015] Preferably, the mass percentage concentration of the sodium tellurite aqueous solution is 1-3wt%.
[0016] Preferably, the mass ratio of the crude product to the sodium tellurite aqueous solution is 1:(3-5).
[0017] Preferably, the particle size of the biomass hard carbon powder is 1500-2000 mesh.
[0018] Preferably, the conductive agent is at least one of carbon nanotubes and acetylene black; and the particle size of the conductive agent is 1500-2500 mesh.
[0019] Preferably, the tackifier is Daicel CMC2200.
[0020] Preferably, the binder is American Solvay PVDF Solef®5130.
[0021] Another object of the present invention is to provide a method for preparing the sodium electric hard carbon negative electrode material using coconut shell as raw material, comprising the following steps: mixing the raw materials evenly by weight, then adding N-methylpyrrolidone thereto, continuing to stir evenly, and then evenly coating the obtained negative electrode slurry on the rough side of the copper foil through a coating machine, and then vacuum drying the coated copper foil at 105-115°C for 18-24h.
[0022] Due to the application of the above technical solution, the present invention has the following beneficial effects: (1) The method for preparing the sodium battery hard carbon negative electrode material using coconut shell as raw material disclosed in the present invention has simple process, convenient operation and control, high preparation efficiency and finished product qualification rate, low dependence on equipment, low energy consumption, suitable for continuous large-scale production, and has high promotion and application value.
[0023] (2) The sodium battery hard carbon negative electrode material using coconut shell as raw material disclosed in the present invention comprises the following raw materials in parts by weight: 100 parts of biomass hard carbon micropowder, 2-4 parts of conductive agent, 3-5 parts of binder, and 0.8-1.2 parts of thickener; the biomass hard carbon micropowder is N / P / Si / S / P / Te / B co-doped hard carbon material micropowder, which is made from coconut shell as raw material; through the mutual coordination and joint action of the raw materials, the prepared negative electrode material has excellent electrochemical performance and good process controllability, and is applied to sodium batteries with large reversible specific capacity, high coulombic efficiency, and excellent cycle performance.
[0024] (3) The sodium-based hard carbon negative electrode material using coconut shell as raw material disclosed in the present invention can reduce the pulverization of the negative electrode caused by sodium ion deintercalation through the reasonable selection of the composition ratio and process parameters of biomass hard carbon micropowder, and has good cycle stability. Through modification and recarbonization, the prepared material can effectively fix the role of sodium salt, ensure the smooth surface sodium intercalation, improve the first coulombic efficiency, and at the same time improve the reversible capacity. The modified modifiers include methacryloxypropyltriethoxysilane, bis(1-vinylimidazole-2-)ketone, 2,4,6-trivinyl cycloboroxine, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, allyltriphenylphosphonium bromide, and sodium tellurite. Through the reasonable selection of the types and proportions of these modifiers, they can cooperate with each other and work together, so that the final product has better electrochemical performance and better process controllability, and the reversible specific capacity, coulombic efficiency and cycle performance used in sodium batteries are better. DETAILED DESCRIPTION
[0025] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1
[0026] A sodium battery hard carbon negative electrode material using coconut shell as raw material is made of the following raw materials in parts by weight: 100 parts of biomass hard carbon micropowder, 2 parts of conductive agent, 3 parts of binder, and 0.8 parts of tackifier.
[0027] The method for preparing the biomass hard carbon micropowder comprises the following steps: Step S1, preparation and activation of coconut shell carbonized material: coconut shell is used as biomass raw material and subjected to high temperature pyrolysis to prepare coconut shell carbonized material; then the coconut shell carbonized material is heated to 550° C. at a heating rate of 6° C. / min, kept warm for 1 hour under a nitrogen atmosphere, cooled to room temperature, then alkali washed, washed with water, dried, and crushed to obtain activated coconut shell carbonized material; Step S2, modification: the activated coconut shell carbonized material prepared in step S1 is dispersed in a high boiling point solvent, and then methacryloxypropyl triethoxysilane, bis(1-vinyl imidazole-2-) ketone, 2,4,6-trivinyl cycloboroxane, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, and initiator are added thereto, and the mixture is stirred and reacted at 60° C. for 3 h in an inert gas atmosphere. After the reaction is completed, the solvent is removed by rotary evaporation; the crude product is then immersed in a sodium telluride aqueous solution at 50° C. for 10 h, and water is removed by rotary evaporation again to obtain the modified coconut shell carbonized material; Step S3, carbonization: the modified coconut shell carbonized material is placed in a muffle furnace, roasted at 200°C for 1 hour, and then kept at 300°C for 2.5 hours, then transferred to a tubular furnace, heated to 800°C under argon atmosphere, kept warm for 1 hour, and then continued to heat to 1210°C and kept warm for 1 hour, and then dry-ground after cooling to obtain biomass hard carbon powder.
[0028] The high temperature pyrolysis in step S1 is specifically as follows: heating to 1000°C at a heating rate of 3°C / min and keeping warm for 1h; the average particle size of the activated coconut shell carbonized material in step S1 is 5μm; the activated coconut shell carbonized material, high boiling point solvent, methacryloxypropyltriethoxysilane, bis(1-vinylimidazole-2-)ketone, 2,4,6-trivinylcycloboroxane, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, initiator The mass ratio of the agent is 3:10:0.1:0.1:0.2:0.1:0.1:0.04; the high boiling point solvent is dimethyl sulfoxide; the initiator is azobisisobutyronitrile; the inert gas is nitrogen; the mass percentage concentration of the sodium telluride aqueous solution is 1wt%; the mass ratio of the crude product and the sodium telluride aqueous solution is 1:3; the particle size of the biomass hard carbon micropowder is 1500 mesh; the conductive agent is carbon nanotubes; the particle size of the conductive agent is 1500 mesh; the thickener is Japan Daicel CMC2200; the binder is American Solvay PVDF Solef®5130.
[0029] A method for preparing a sodium electric hard carbon negative electrode material using coconut shell as a raw material comprises the following steps: uniformly mixing the raw materials by weight, then adding N-methylpyrrolidone thereto, continuing to stir uniformly, then uniformly coating the obtained negative electrode slurry on the rough side of a copper foil through a coating machine, and then vacuum drying the coated copper foil at 105°C for 18 hours. Example 2
[0030] A sodium battery hard carbon negative electrode material using coconut shell as raw material is made of the following raw materials in parts by weight: 100 parts of biomass hard carbon powder, 2.5 parts of conductive agent, 3.5 parts of binder, and 0.9 parts of tackifier.
[0031] The method for preparing the biomass hard carbon micropowder comprises the following steps: Step S1, preparation and activation of coconut shell carbonized material: coconut shell is used as biomass raw material and subjected to high temperature pyrolysis to prepare coconut shell carbonized material; then the coconut shell carbonized material is heated to 600°C at a heating rate of 6.5°C / min, kept warm for 1.5h under a nitrogen atmosphere, cooled to room temperature, then alkali washed, washed with water, dried, and crushed to obtain activated coconut shell carbonized material; Step S2, modification: the activated coconut shell carbonized material prepared in step S1 is dispersed in a high boiling point solvent, and then methacryloxypropyl triethoxysilane, bis(1-vinyl imidazole-2-) ketone, 2,4,6-trivinyl cycloboroxane, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, and initiator are added thereto, and the mixture is stirred and reacted at 63° C. for 4 hours in an inert gas atmosphere. After the reaction is completed, the solvent is removed by rotary evaporation; the crude product is then immersed in a sodium telluride aqueous solution at 53° C. for 12 hours, and water is removed by rotary evaporation again to obtain the modified coconut shell carbonized material; Step S3, carbonization: the modified coconut shell carbonized material is placed in a muffle furnace, roasted at 205°C for 1.5 hours, and then kept at 310°C for 3 hours, and then transferred to a tubular furnace, heated to 820°C under argon atmosphere, kept warm for 1.2 hours, and then continued to heat to 1250°C and kept warm for 1.2 hours. After cooling, dry grinding is performed to obtain biomass hard carbon powder.
[0032] The high temperature pyrolysis in step S1 is specifically as follows: heating to 1100°C at a heating rate of 4°C / min and keeping warm for 1.2h; the average particle size of the activated coconut shell carbonized material in step S1 is 6μm; the mass ratio of the activated coconut shell carbonized material, high boiling point solvent, methacryloxypropyl triethoxysilane, bis(1-vinyl imidazole-2-) ketone, 2,4,6-trivinyl cycloboroxane, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, and initiator in step S2 is 3.5 :13:0.15:0.1:0.2:0.1:0.1:0.045; the high boiling point solvent is N,N-dimethylformamide; the initiator is azobisisobutyronitrile; the inert gas is helium; the mass percentage concentration of the sodium telluride aqueous solution is 1.5wt%; the mass ratio of the crude product and the sodium telluride aqueous solution is 1:3.5; the particle size of the biomass hard carbon micropowder is 1700 mesh; the conductive agent is at least one of acetylene black; the particle size of the conductive agent is 1800 mesh; the thickener is Japan Daicel CMC2200; the binder is American Solvay PVDF Solef®5130.
[0033] A method for preparing a sodium electric hard carbon negative electrode material using coconut shell as a raw material comprises the following steps: mixing the raw materials uniformly by weight, then adding N-methylpyrrolidone thereto, continuing to stir uniformly, then coating the obtained negative electrode slurry uniformly on the rough side of a copper foil through a coating machine, and then vacuum drying the coated copper foil at 109°C for 20 hours. Example 3
[0034] A sodium battery hard carbon negative electrode material using coconut shell as raw material is made of the following raw materials in parts by weight: 100 parts of biomass hard carbon micropowder, 3 parts of conductive agent, 4 parts of binder and 1 part of tackifier.
[0035] The method for preparing the biomass hard carbon micropowder comprises the following steps: Step S1, preparation and activation of coconut shell carbonized material: coconut shell is used as biomass raw material and subjected to high temperature pyrolysis to prepare coconut shell carbonized material; then the coconut shell carbonized material is heated to 630° C. at a heating rate of 7° C. / min, kept warm for 2 h in a nitrogen atmosphere, cooled to room temperature, then alkali washed, washed with water, dried, and crushed to obtain activated coconut shell carbonized material; Step S2, modification: the activated coconut shell carbonized material prepared in step S1 is dispersed in a high boiling point solvent, and then methacryloxypropyl triethoxysilane, bis(1-vinyl imidazole-2-) ketone, 2,4,6-trivinyl cycloboroxane, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, and initiator are added thereto, and the mixture is stirred and reacted at 65° C. for 4.5 hours in an inert gas atmosphere. After the reaction is completed, the solvent is removed by rotary evaporation; the crude product is then immersed in a sodium telluride aqueous solution at 55° C. for 15 hours, and water is removed by rotary evaporation again to obtain the modified coconut shell carbonized material; Step S3, carbonization: the modified coconut shell carbonized material is placed in a muffle furnace, roasted at 210°C for 2 hours, and then kept at 315°C for 3.2 hours, then transferred to a tubular furnace, heated to 830°C under argon atmosphere, kept warm for 1.5 hours, and then continued to heat to 1270°C and kept warm for 1.5 hours. After cooling, dry grinding is performed to obtain biomass hard carbon powder.
[0036] The high temperature pyrolysis in step S1 is specifically as follows: heating to 1180°C at a heating rate of 4.5°C / min and keeping warm for 1.5h; the average particle size of the activated coconut shell carbonized material in step S1 is 8μm; the activated coconut shell carbonized material in step S2, high boiling point solvent, methacryloxypropyl triethoxysilane, bis(1-vinyl imidazole-2-) ketone, 2,4,6-trivinyl cycloboroxane, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, initiator The mass ratio of the agent is 4:15:0.2:0.1:0.2:0.1:0.1:0.05; the high boiling point solvent is N-methylpyrrolidone; the initiator is azobisisobutyronitrile; the inert gas is neon; the mass percentage concentration of the sodium telluride aqueous solution is 2wt%; the mass ratio of the crude product and the sodium telluride aqueous solution is 1:4; the particle size of the biomass hard carbon micropowder is 1800 mesh; the conductive agent is carbon nanotubes; the particle size of the conductive agent is 2000 mesh; the thickener is Japan Daicel CMC2200; the binder is American Solvay PVDF Solef®5130.
[0037] A method for preparing a sodium electric hard carbon negative electrode material using coconut shell as raw material comprises the following steps: mixing the raw materials uniformly by weight, then adding N-methylpyrrolidone thereto, continuing to stir uniformly, then coating the obtained negative electrode slurry uniformly on the rough side of a copper foil through a coating machine, and then vacuum drying the coated copper foil at 110°C for 21 hours. Example 4
[0038] A sodium battery hard carbon negative electrode material using coconut shell as raw material is made of the following raw materials in parts by weight: 100 parts of biomass hard carbon powder, 3.5 parts of conductive agent, 4.5 parts of binder, and 1.1 parts of tackifier.
[0039] The method for preparing the biomass hard carbon micropowder comprises the following steps: Step S1, preparation and activation of coconut shell carbonized material: coconut shell is used as biomass raw material and subjected to high temperature pyrolysis to prepare coconut shell carbonized material; then the coconut shell carbonized material is heated to 680°C at a heating rate of 7.5°C / min, kept warm for 2.5h under a nitrogen atmosphere, cooled to room temperature, then alkali washed, washed with water, dried, and crushed to obtain activated coconut shell carbonized material; Step S2, modification: the activated coconut shell carbonized material prepared in step S1 is dispersed in a high boiling point solvent, and then methacryloxypropyl triethoxysilane, bis(1-vinyl imidazole-2-) ketone, 2,4,6-trivinyl cycloboroxane, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, and initiator are added thereto, and the mixture is stirred and reacted at 68° C. for 5.5 hours in an inert gas atmosphere. After the reaction is completed, the solvent is removed by rotary evaporation; the crude product is then immersed in a sodium telluride aqueous solution at 58° C. for 18 hours, and water is removed by rotary evaporation again to obtain the modified coconut shell carbonized material; Step S3, carbonization: the modified coconut shell carbonized material is placed in a muffle furnace, roasted at 215°C for 2.5 hours, and then kept at 325°C for 3.8 hours, and then transferred to a tubular furnace, heated to 850°C under an argon atmosphere, kept warm for 1.8 hours, and then continued to heat to 1320°C and kept warm for 1.8 hours. After cooling, dry grinding is performed to obtain biomass hard carbon powder.
[0040] The high temperature pyrolysis in step S1 is specifically as follows: heating to 1250°C at a heating rate of 5.5°C / min and keeping warm for 1.8h; the average particle size of the activated coconut shell carbonized material in step S1 is 9μm; the mass ratio of the activated coconut shell carbonized material, high boiling point solvent, methacryloxypropyltriethoxysilane, bis(1-vinylimidazole-2-)ketone, 2,4,6-trivinylcycloboroxane, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, and initiator in step S2 is 4.5:18:0.25:0.1:0.2: 0.1:0.1:0.055; the high boiling point solvent is a mixture of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone in a mass ratio of 1:1:3; the initiator is azobisisobutyronitrile; the inert gas is argon; the mass percentage concentration of the sodium telluride aqueous solution is 2.5wt%; the mass ratio of the crude product to the sodium telluride aqueous solution is 1:4.5; the particle size of the biomass hard carbon powder is 1900 mesh; the conductive agent is a mixture of carbon nanotubes and acetylene black in a mass ratio of 3:5; the particle size of the conductive agent is 2400 mesh; the tackifier is Japan Daicel CMC2200; the binder is American Solvay PVDF Solef®5130.
[0041] A method for preparing a sodium electric hard carbon negative electrode material using coconut shell as a raw material comprises the following steps: mixing the raw materials uniformly by weight, then adding N-methylpyrrolidone thereto, continuing to stir uniformly, then coating the obtained negative electrode slurry uniformly on the rough side of a copper foil through a coating machine, and then vacuum drying the coated copper foil at 113°C for 23 hours. Example 5
[0042] A sodium battery hard carbon negative electrode material using coconut shell as raw material comprises the following raw materials in parts by weight: 100 parts of biomass hard carbon powder, 4 parts of conductive agent, 5 parts of binder and 1.2 parts of viscosity enhancer.
[0043] The method for preparing the biomass hard carbon micropowder comprises the following steps: Step S1, preparation and activation of coconut shell carbonized material: coconut shell is used as biomass raw material and subjected to high temperature pyrolysis to prepare coconut shell carbonized material; then the coconut shell carbonized material is heated to 700°C at a heating rate of 8°C / min, kept warm for 3 hours under a nitrogen atmosphere, cooled to room temperature, then alkali washed, washed with water, dried, and crushed to obtain activated coconut shell carbonized material; Step S2, modification: the activated coconut shell carbonized material prepared in step S1 is dispersed in a high boiling point solvent, and then methacryloxypropyl triethoxysilane, bis(1-vinyl imidazole-2-) ketone, 2,4,6-trivinyl cycloboroxane, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, and initiator are added thereto, and the mixture is stirred and reacted at 70° C. for 6 hours in an inert gas atmosphere. After the reaction is completed, the solvent is removed by rotary evaporation; the crude product is then immersed in a sodium telluride aqueous solution at 60° C. for 20 hours, and water is removed by rotary evaporation again to obtain the modified coconut shell carbonized material; Step S3, carbonization: the modified coconut shell carbonized material is placed in a muffle furnace, roasted at 220°C for 3 hours, and then kept at 330°C for 4 hours, and then transferred to a tubular furnace, heated to 860°C under an argon atmosphere, kept warm for 2 hours, and then continued to heat to 1330°C and kept warm for 2 hours. After cooling, dry grinding is performed to obtain biomass hard carbon powder.
[0044] The high temperature pyrolysis in step S1 is specifically as follows: heating to 1300°C at a heating rate of 6°C / min and keeping warm for 2h; the average particle size of the activated coconut shell carbonized material in step S1 is 10μm; the activated coconut shell carbonized material, high boiling point solvent, methacryloxypropyltriethoxysilane, bis(1-vinylimidazole-2-)ketone, 2,4,6-trivinylcycloboroxane, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, and the quality of the initiator are as follows: The molecular weight ratio is 5:20:0.3:0.1:0.2:0.1:0.1:0.06; the high boiling point solvent is N,N-dimethylformamide; the initiator is azobisisobutyronitrile; the inert gas is argon; the mass percentage concentration of the sodium telluride aqueous solution is 3wt%; the mass ratio of the crude product and the sodium telluride aqueous solution is 1:5; the particle size of the biomass hard carbon micropowder is 2000 mesh; the conductive agent is carbon nanotubes; the particle size of the conductive agent is 2500 mesh; the thickener is Japan Daicel CMC2200; the binder is American Solvay PVDF Solef®5130.
[0045] A method for preparing a sodium electric hard carbon negative electrode material using coconut shell as a raw material comprises the following steps: uniformly mixing the raw materials by weight, then adding N-methylpyrrolidone thereto, continuing to stir uniformly, then uniformly coating the obtained negative electrode slurry on the rough side of a copper foil through a coating machine, and then vacuum drying the coated copper foil at 115°C for 24 hours.
[0046] Comparative Example 1 A sodium electric hard carbon negative electrode material using coconut shell as raw material and a preparation method thereof, which is basically the same as Example 1, except that the process of soaking in a sodium tellurite aqueous solution is not added.
[0047] Comparative Example 2 A sodium electric hard carbon negative electrode material using coconut shell as raw material and a preparation method thereof, which is basically the same as Example 1, except that 2,4,6-trivinyl cycloboroxine and 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt are not added.
[0048] In order to further illustrate the beneficial technical effects of the sodium-electric hard carbon negative electrode material using coconut shell as raw material involved in each embodiment of the present invention, relevant performance tests were carried out on the sodium-electric hard carbon negative electrode material using coconut shell as raw material involved in Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1. The test method is as follows: the hard carbon negative electrode material prepared in each example was cut into 16 mm discs as negative electrode sheets, a metal sodium sheet was used as a counter electrode, a Whatman glass fiber filter membrane was used as a diaphragm, 1 mol / L NaPF6 (the volume ratio of ethylene carbonate EC and diethyl carbonate DEC was 1:1) was used as a solvent, and fluoroethylene carbonate FEC was used as an additive as an electrolyte, and a CR2032 battery was assembled in an argon-filled glove box; the battery prepared above was subjected to charge and discharge cycle tests using a CT2001A blue electric system, with a discharge cut-off voltage of 0 V and a charge cut-off voltage of 2 V, and the first reversible specific capacity, the first coulomb efficiency and the capacity retention rate after 100 cycles were tested.
[0049] Table 1 project First reversible specific capacity First coulombic efficiency Capacity retention rate after 100 cycles unit <![CDATA[mAh·g -1 ]]> % % Example 1 382 92.1 86.8 Example 2 385 92.5 87.4 Example 3 387 92.7 87.8 Example 4 388 92.9 88.2 Example 5 390 93.2 88.7 Comparative Example 1 375 90.3 84.7 Comparative Example 2 370 89.6 83.6 As can be seen from Table 1, the sodium electric hard carbon negative electrode material using coconut shell as raw material disclosed in the embodiment of the present invention has better electrochemical performance than the comparative example product; it has large reversible specific capacity, high coulombic efficiency and excellent cycle performance when applied to sodium batteries; in the process of soaking in sodium tellurite aqueous solution, the combined use of 2,4,6-trivinyl cycloboroxine and 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt is beneficial to improving the above performance.
[0050] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A sodium electric hard carbon negative electrode material using coconut shell as raw material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of biomass hard carbon powder, 2-4 parts of conductive agent, 3-5 parts of binder, and 0.8-1.2 parts of tackifier; The method for preparing the biomass hard carbon micropowder comprises the following steps: Step S1, preparation and activation of coconut shell carbonized material: using coconut shell as biomass raw material and subjecting it to high temperature pyrolysis to prepare coconut shell carbonized material; then heating the coconut shell carbonized material to 550-700°C at a heating rate of 6-8°C / min, keeping the temperature for 1-3h under a nitrogen atmosphere, cooling to room temperature, then alkali washing, water washing, drying, and crushing to obtain activated coconut shell carbonized material; Step S2, modification: the activated coconut shell carbonized material prepared in step S1 is dispersed in a high boiling point solvent, and then methacryloxypropyl triethoxysilane, bis(1-vinyl imidazole-2-) ketone, 2,4,6-trivinyl cycloboroxane, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, and initiator are added thereto, and the mixture is stirred and reacted at 60-70° C. for 3-6 hours in an inert gas atmosphere. After the reaction is completed, the solvent is removed by rotary evaporation; the crude product is then immersed in a sodium telluride aqueous solution at 50-60° C. for 10-20 hours, and water is removed by rotary evaporation again to obtain the modified coconut shell carbonized material; Step S3, carbonization: the modified coconut shell carbonized material is placed in a muffle furnace, roasted at 200-220°C for 1-3h, and then kept at 300-330°C for 2.5-4h, then transferred to a tubular furnace, heated to 800-860°C under argon atmosphere, kept warm for 1-2h, and then continued to heat to 1210-1330°C for 1-2h, cooled and dry ground to obtain biomass hard carbon powder.
2. The sodium electric hard carbon negative electrode material using coconut shell as raw material according to claim 1, characterized in that: The high temperature pyrolysis in step S1 is specifically: heating to 1000-1300° C. at a heating rate of 3-6° C. / min, and keeping the temperature for 1-2 hours.
3. The sodium electric hard carbon negative electrode material using coconut shell as raw material according to claim 1, characterized in that: The average particle size of the activated coconut shell carbonized material in step S1 is 5-10 μm.
4. The sodium electric hard carbon negative electrode material using coconut shell as raw material according to claim 1, characterized in that: The mass ratio of the activated coconut shell carbonized material, high boiling point solvent, methacryloxypropyl triethoxysilane, bis(1-vinyl imidazole-2-) ketone, 2,4,6-trivinyl cycloboroxine, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, allyl triphenylphosphine bromide, and initiator in step S2 is (3-5):(10-20):(0.1-0.3):0.1:0.2:0.1:0.1:(0.04-0.06).
5. The sodium electric hard carbon negative electrode material using coconut shell as raw material according to claim 1, characterized in that: The high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone; the initiator is azobisisobutyronitrile; and the inert gas is any one of nitrogen, helium, neon, and argon.
6. The sodium electric hard carbon negative electrode material using coconut shell as raw material according to claim 1, characterized in that: The mass percentage concentration of the sodium tellurite aqueous solution is 1-3wt%; the mass ratio of the crude product to the sodium tellurite aqueous solution is 1:(3-5).
7. The sodium electric hard carbon negative electrode material using coconut shell as raw material according to claim 1, characterized in that: The particle size of the biomass hard carbon powder is 1500-2000 meshes.
8. The sodium electric hard carbon negative electrode material using coconut shell as raw material according to claim 1, characterized in that: The conductive agent is at least one of carbon nanotubes and acetylene black; the particle size of the conductive agent is 1500-2500 meshes.
9. The sodium electric hard carbon negative electrode material using coconut shell as raw material according to claim 1, characterized in that: The tackifier is Japan Daicel CMC2200; the binder is American Solvay PVDF Solef®5130.
10. A method for preparing a sodium electric hard carbon negative electrode material using coconut shell as raw material according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: uniformly mixing the raw materials by weight, then adding N-methylpyrrolidone thereto, continuing to stir uniformly, then uniformly coating the obtained negative electrode slurry on the rough surface of the copper foil through a coating machine, and then vacuum drying the coated copper foil at 105-115°C for 18-24h.
Citation Information
Patent Citations
A hard carbon negative electrode material for sodium ion battery and preparation method thereof
CN116344803B
Composite ultrafiltration membrane and preparation method thereof
CN118045490A
Easy-to-clean coating as well as preparation method and application thereof
CN118240452A
Flame-retardant inorganic quick-setting material and preparation method thereof
CN119430821A
Cited By
Sodium secondary battery, coconut shell-based hard carbon negative electrode active material, negative electrode material, negative electrode, preparation method and application thereof
CN121812537A